You are on page 1of 39

x+5=3,

3x=7 ...,

x 2 =-3,
...
i :
i 2 =-1 . i,
, ,
+i
(complex ,

)
i: i 0 1, i 1 i , i 2 1, i 3 i

i i 4

1
i

i
-1
i

,
,

0
1

, 2
,


={xi/x}
C={+i/,}

, ,

.
z=+i, =Re(z) :
=m(z) :
z=+i (,)
(,).
z OM z ,


.

+i=+i= =
(+i)(+i)=()+()i
(+i)(+i)=(-)+(+)i

i
i

i 2 2 2 2
z=+i z =-i

z+ z =2, z- z =2i

z1 z 2 z1 z 2 , z 1 z 2 z1 z 2 , ( z ) z
z
z1 z 2 z1 z 2 , 1
z2

z1

, ( z ) ( z )
z
2

z1 z 2 z z1 z 2 z z 1 z 2 ... z z 1 z 2 ... z
: ,
,
.
: z= z z, z=- z z
: z,
yy ,
-z xx
- z
:
z= OM z =d(O,M z )= 2 2
z-w=d( z , w )

| z | | z | | z | , | z1 z 2 | | z1 | | z 2 | ,

z1
z
1
z2
z2

, | z | | z | ,

| | z 1 | | z 2 | | | z1 z 2 | | z1 | | z 2 |
z 2 =z z
,
<0 :

z1,2

i
2

:
z-z0=>0 z
z0
3

z-z1=z-z2 z
z1 z2.

z-z1+z=z2=
z-z1-z=z2= .
z
z x+yi (x,y)
.


f

.
f(x)=y x ( )
y (
) .

,
.
f
f.
, f().
f, g ..
f(x)=g(x), x
, .. ,

,
.

.
, , x
f(x).
, .

,
5

.
,

.
..
4x 1, x 2
x x 1

f (x )
, .. f ( x ) 3, 2 x 4
x x
e
x , x 7



x f(x) y.


.. xy=1, x(-,-1][1,+) y ,
2 2
y,
x y=f(x) .
, ..
.
f
Oxy M ( x, (f ( x ))
x A . , M ( x , y)
f, y f ( x )


f .. :
x -x f(-x)=f(x)
x -x f(-x)=-f(x)
6

1-1 x1,x2, x1x2, f(x1)f(x2) f(x1)=f(x2),


x1=x2
x1,x2, x1<x2, f(x1)<f(x2)
x1,x2, x1<x2, f(x1)>f(x2)
f :
() x1 A , f ( x ) f ( x1 ) x
() x 2 A , f ( x ) f ( x 2 ) x

x1 , f ( x ) f ( x1 ) x
x1
x 2 f ( x ) f ( x 2 ) x
x 2 .


.. f g xg, g(x)f
x f g f g(x)=f(g(x))

f 1-1,
f -1 :
f (A) f,
f
:

f ( x ) y f 1 ( y) x .
:

f (x) y f 1 (y) x ,x f(f-1(y))=y,yf()


C C f f 1
y x
xOy xOy




.
( C.W. Leadbeater)
x0
, x x0.
,
, x0.
, x
x0, .
x x0
. :

lim f ( x ) ,

xx 0

lim f ( x ) lim f ( x )

x x 0

xx 0

,
:
)
.
)
( 00 , , 0 , ).

.
, :
! ;
,
De l Hospital.
9

)
. 0 0 .
,
f
1

f
g
g

10


) f(x)g(x) x0 f, g x0,
lim f ( x ) lim g( x )
x x 0

xx0

f, g x0,
.


, ,
!
) ()
lim f ( x ) 0 , f(x)>0 x 0
xx 0

lim f ( x ) 0 , f ( x ) 0
xx 0

x 0

: .

x0. , x0,
,
x0 .
)
h ( x ) f ( x ) g ( x ) x 0

lim h(x) lim g(x) , lim f ( x) .

x x0

x x0

x x0

: ,
.

(.. f) (.. g)
11

x0, .
.
:

lim( 3 x 2 x ) 3

x 1
1
x


3 x11 3 x11
g(x),
3+1=4,
f(x)g(x)f(x)
( 3 x 2 x )3 x11 =
= ( 3 x 2 x ) 3 x11
( 3 x 2 x) 4


:
x-x
=f(x)

f
,

- ( 3 x 2 x ) 4 f(x)
4 ( 3 x 2 x)

lim ( Kf ( x )) 0

x x 0

lim (Kf ( x )) 0

x x0

lim f ( x ) 0
x x
0

lim 4( 3 x 2 x) 0
x 1

lim 4( 3 x 2 x) 0 ,
x 1

lim f (x) 0
x 1

12

()
g(x) u

lim f (g ( x ))

xx0

lim u u 0

lim f (u )

u u 0

xx0

!
:
1.

2.

u0.

3.

u.

:
x0
.

x
x 1
1,
lim
0 ,
x

0
x
x
x0
!
: lim
x 0

x0.
x0
.

.


De L Hospital.
, ,
.

13


1.

0
0

) De L Hospital
)
.
) .
)
. (:
),
(
) :

AB

A 2 B2
A 2 B2
AB
AB
AB

AB

A 3 B3
A 3 B3

A
B
A 2 AB B 2
A 2 AB B 2

AB

A B
A 2 B ... B 1

:

x0 .. .

14

2.

:
0

, f ( x ) 0 x 0

, f ( x ) 0 x 0
lim
xx 0 f ( x )
, f


1


f (x)
( ).
f

>0 <0 >0 <0

fg +

f+g

, x0,
: + -.

15


: lim

: lim

1
0 , lim f ( x )
x
f (x )

1
0 , n 0
xn

lim x 0, 0 1, lim x 0, 1

lim x , 1, lim x , 0 1

lim ln x , lim ln x

x 0

:
,
,

.
:
x.
1
x 2 (1 2 ) 2x 2
x 2 1 2x 2
x
.. lim
lim

2
x
x
3
x x 3
2
x x (1 2 )
x

16

(1 1 )

2
x
2
x
2
x
1

x (1 2 ) 2x 2
x 0
x

lim
lim
x
x

3
3
x x (1 2 )
x 1 (1 2 )

x
x

(1 1 )

2
x 2
x

(2)

lim

x

(1 0 )
3
1 (1 )

x 2

x
. ..
x

2
lim (2 x 3x ) lim 3x ( 1)
x
x
3
,
, , ,
.
(
)

(x) x0,

.
.. g(x)
17

,
.
-
x0 .

lim

xx 0

f (x )
l lim g( x ) 0 :
xx 0
g( x )

lim f ( x ) lim

xx 0

xx 0

f (x )
g( x ) l 0 0
g( x )


f x0 lim f ( x ) f ( x 0 )
xx 0

f .
,
, ,

(, ,
) ,

.

18

:
1. Bolzano
f [, ] f () f () 0 ,
, , x 0 (, ) , f ( x 0 ) 0 .
2. f
,
.
3.
f [, ] f ( ) f ( )
, f () f ( )
, x 0 (, ) , f ( x 0 )
4. f ()
f .
5. f [, ] , f
[, ] m
6.
:

[,]

(,)

[,)

(,]

[f(),f()]

(,)

[f(),)

(,f()]

[f(),f()]

(,)

(,f()]

[f(),)

19

= lim f ( x ) , = lim f ( x )
x

(
,
.)

20


f x0 ..
f(x0)
f ( x) f (x 0 )

f ( x 0 ) lim
x x 0
x x0
.

f (x 0 h) f ( x 0 )
h 0
h

f ( x 0 ) lim

: f , ,
.
x0
(x0,f(x0)),

y=f(x) x, x=x0.
f

() f.

21

(c) 0
( x ) 1

(cf ( x )) cf ( x )

( x ) x 1
( x )

2 x
(x ) x
(x ) x
1
(x)=
2 x
1
(x)= 2
x

(f ( x ) g ( x )) f ( x ) g( x )
(f ( x )g( x )) f ( x )g ( x ) f ( x )g( x )

f ( x ) f ( x )g( x ) f ( x )g( x )

(g ( x )) 2
g(x )

f (g( x )) f (g( x )) g (x)

(e x ) e x
(x)= xln
1
(nx )
x

Rolle
f :
[, ]
(, )
f () f ()
, , (, ) , :

f () 0

22

()
f : [,]
[,]
(,)
, , , : f ( )

f () f ()


f .
1) f f ( x) 0
x , f .
2) f,g f ( x ) g( x )
x , f=g+c .
3) f f ( x ) 0
x , f .
4) f f ( x ) 0
x , f

.
(Fermat)
f x0
. f
x0 , : f(x0)=0
:
f
:
23

1. f
.
2. f .
3. ( ).
f
,
f .
:
f(x) x, f ,
f() , f()=0

.
f

x
0
-
f(x)
f(x)
0
f
+

1
+
0
+

+
-

f
0 !
:

f ( , )

x 0 ( , ) f
.
f (x 0 ) 0 f (x 0 ) 0 , f (x 0 ) .
24

f (x 0 ) 0 f (x 0 ) 0 , f (x 0 )
.

f
. :
f
, f .
f
, f .

.

f (, ) ,
x 0 .
f (, x 0 ) ( x 0 , ) ,
,
Cf A(x 0 , f (x 0 )) ,
A(x 0 , f (x 0 ))
f.

A(x 0 , f (x 0 ))
f f , f (x 0 ) 0 .

25

Fermat,
.
.
f
:
i) f ,
ii) f

.

1. lim f (x) , lim f (x)


x x0

x x0

, x x 0
f.
2. lim f (x) (
x

lim f (x) ) ,

y
f ( ).

3. y x
f , ,

lim [ f ( x) ( x )] 0 ,

lim [ f ( x) ( x )] 0 .

26

y x

f , ,

lim

f (x)
! lim [f ( x ) x ] ! ,
x
x

lim

f (x)
! lim [f ( x ) x ] ! .
x
x

-
0

f (x) 0 ,
f (x)
1. de lHospital lim

lim
, x 0 ,
x g(x)
x g(x)

.
2. (0) de lHospital fg
f

1
g
3. fg
: fg=eglnf

27

f (x)dx F(x) c

() f
c .

0
x,-1

1
x

c
1
x
1
lnx

f (x)dx F(x)

F() F()

F f

.

1
x
1
2 x

-x

1
2 x

1
2 x

-x

ex

ex

x
ln

f (x)dx f (x) c

f (x)dx f () f ()

f (x)dx f (x)dx

f (x)dx f (x)dx

( f (x) g(x))dx f (x)dx g(x)dx (f(x) g(x))dx f(x)dx g(x)dx

28

f (x)dx 0 ,

f (x)dx f (x)dx

f (x)dx f (x)dx f (x)dx

f(x)g(x)f(x)g(x)dx
f(x)g(x)dx

[f(x)g(x)] f(x)g(x)dx
f(x)g(x)dx

u
f (g(x))g (x)dx f (u)du ,
f (g(x))g (x)dx u f (u)du
u=g(x), du=g(x)dx
u ,u
2

, g.
:
1.
, u .

x 2 1 x 1x
1
x2 1

e
dx

x
...

2
x
x
x2

1
x
1
x =u, e u du e x c
x
2.

.
.
3.
=u.
2- x2 (
x
u
) x=u, u(0,).
1
/2
1
0
0
..
4 x 2 dx x=2u, u(0,)
..

dx=-2udu, 0,/2 4-42u=42u


29

4 udu
2

= ...

4. x2+2

x=u, u , .
2 2
3
1

dx u=3x, x , , 0
.. 2
x

9
2 2
0
2
1, dx=3(1+ u)du :
1
1
1
2
0 9u 2 9 (1 u)du 9
5. x, x,

u .
2 x
..
dx x , u=x.
x
du=-xdx. du
-x:

2 x
(x)dx u,
2 x
, 2x=1-2x=1-u2.
6. x, x,
,
1 2
1 2
, 2
, =1/2 2
2
2
2
1
,
1 2 x (x) ,
2 x
: u=x.
30

f ( x)dx 0 (: <!) f

0 [,]
f(x)g(x) x [,]
[,], f=g
, :

f ( x )dx g( x )dx

f [, ] ,
, , (, ) ,

f ( )

f (x)dx f ()( )

f (x)dx

[, ] f

F(x)

f (t )dt , x ()

f , :

x
f (t)dt f (x)

:
1.
, F.
To x ,
, . F .
31

t
, , !
2.

3.

g( x )

f (t)dt

f (t)dt

4.

g(x )

h (x )

f (t)dt

f (g(x))g(x)

f (t)dt

g(x )

f (x)

f (t)dt

h (x )

f (t)dt

f (g(x))g(x) g(h(x))h (x)


x.
x
.
x
, x .
:
x ,
.
..

xf (t)dt x f (t)dt x f (t)dt x f (t)dt


x

xf (t)dt +xf(x)

x ( t)
:

32

F(x)=

f ( xt )dt , x>>0 u=xt, du=xdt

x2

x2

x
x2
f (u )du
f ( xt )
f (u )
=
F(x)=
xdt
du , F(x)= x

x
x
x

xx,
. . () f x=, x= (<) :

E ( )

f (x) dx

. .
() f,g x=, x= (<) :

E ( )

f (x) g(x) dx



,
.

33

= [h ( x ) f ( x )]dx [g ( x ) f ( x )]dx

34




. ,
.
1. .
:
x2

1.

(t)dt 1 x 2 , f

2. x4=4x, x>e
1

()



.

:
x2

(t)dt (x 2 1) 0 , :

x2

(x)=

(t)dt (x 2 1)

.
(x)=2xf2(x)+2x=2x[f2(x)+1]
0
x
-
(x)
(x)



+

+

.
,
,
35

. x=1 x=-1.
(-1)=(1)=0,
1

2


,

.

ln x ln 4

x
4
f(x)=f(4),
ln x
,x>e
f f(x)=
x
1 ln x

f (x)
x2
x>e , f
x=4
.
x4=4x4lnx=xln4

f
1-1 (.. . ,
),

.

2.
.

f((x))>f((x))
.
x4>4x, x>e f(x)>f(4)
x<4
e<x<4.
:

ex

x 1

x2 x e

f (x) e x
2

x 1

(x 2 x e)

f (x) (2x 1)(e x x 1 1) :


x

-
+
+
f(x)
f(x)

36


f ,
.
0 1 f(0)=0=f(1)
x
0

1
-
+
+
f(x)
f(x)
0
0

(1,+ ) .
3. :
)
)
) 2 .
4.





(...)'=0 (...)'=(...)'
: .

...,



,

,



(
)

37

;
.


;
5. 1
:
. Bolzano
:


. Rolle


(Rolle, Bolzano,
... .
)
:

!
6. 1
:
1
.
. Rolle
7.




,
,
.




.





,
(Q(x),

x

f (x) f (x 0 ) Q(t)dt
.
x0
,



.

(


)

38